Pengaruh Ukuran Perusahaan, Profitabilitas, Ukuran Kantor Akuntan Publik (Kap), Dan Kompleksitas Terhadap Audit Report Lag - Ivana Nurhidayati; Mohamad Rafki Nazar; Febrial Pratama (UNHI Press, 2021)
The purpose of this research to determine the simultaneous and partial effects of the variables of company size, profitability, KAP size, and complexity on audit report lag. This research method is quantitative. The research used purposive sampling technique in obtaining samples. There were 35 samples that were observed for four years, and obtained a sample of 140 mining sector companies listed on the IDX during the 2016-2019 period. Regression analysis is panel data using software E-Views 11. This study can show that partially company size and complexity have positive effect on audit report lag, profitability has negative effect on audit report lag, while KAP size has no effect on audit report lag.